Ranolazine for Symptomatic Management of Microvascular Angina. (March 2020) - Rayner-Hartley, Erin; Parvand, Mahraz; Humphries, Karin H.; Starovoytov, Andrew; Park, Julie E.; Sedlak, Tara
Abstract : Background: Ranolazine is approved in the United States and Europe for chronic stable angina. Microvascular angina (MVA) is defined as angina with no obstructive coronary artery disease. Study Question: Our objective was to assess the effectiveness of ranolazine at improving angina scores and quality of life in a Canadian cohort with severe refractory angina due to MVA. Study Design: We administered questionnaires to 31 patients at baseline and after at least 6 weeks of ranolazine treatment. Measures and Outcomes: Validated, clinically significant changes for each Seattle Angina Questionnaire domain and the Quality of Life Enjoyment and Satisfaction Questionnaire Short Form were obtained from the literature. Score changes between baseline and postranolazine use were analyzed using sign test. Results: Patients were mostly female (27 of 31 patients) with a median age of 57 years. After initiation of ranolazine treatment, patients experienced improvements in Quality of Life Enjoyment and Satisfaction Questionnaire Short Form scores (80.6%; P < 0.01) and in 3 of the 4 domains of the Seattle Angina Questionnaire (physical limitation: 73.3%; P = 0.02; treatment satisfaction: 80.6%; P < 0.01; and disease perception: 77.4%; P < 0.01). Patients were less likely to have interactions with the health care system after ranolazine treatment as compared with before (35.5% vs. 93.5%; P < 0.01). Conclusions: Ranolazine significantly improves symptom control and quality of life in patients with MVA and severe refractory angina and reduces their interaction with the health care system. Given the potentially debilitating effect of chronic angina in MVA, ranolazine may be an effective treatment option.